Levels of oxidative stress biomarkers and bone resorption regulators in apical periodontitis lesions infected by Epstein–Barr virus. (30th January 2018) - Jakovljevic, A.; Andric, M.; Nikolic, N.; Coric, V.; Krezovic, S.; Carkic, J.; Knezevic, A.; Beljic‐Ivanovic, K.; Pljesa‐Ercegovac, M.; Miletic, M.; Soldatovic, I.; Radosavljevic, T.; et al.
Abstract: Aim: To investigate whether apical periodontitis lesions infected by Epstein–Barr virus (EBV) exhibit higher levels of oxidative stress biomarkers [8‐hydroxydeoxyguanosine (8‐OHdG) and oxidized glutathione (GSSG)] and bone resorption regulators [receptor activator of nuclear factor (NF‐κB) ligand (RANKL) and osteoprotegerin (OPG)] compared to EBV‐negative periapical lesions and healthy pulp tissues. Methodology: The experimental group consisted of 30 EBV‐positive and 30 EBV‐negative periapical lesions collected in conjunction with apicoectomy. The pulp tissues of 20 impacted third molars were used as healthy controls. The qualitative and quantitative analysis of EBV was performed by nested and real‐time polymerase chain reaction (PCR), respectively. The levels of RANKL and OPG were analysed by reverse transcriptase real‐time PCR. The levels of 8‐OHdG and GSSG were determined by enzyme‐linked immunosorbent assay (ELISA). Mann–Whitney U ‐test and Spearman's correlation were used for statistical analysis. Results: The levels of RANKL, OPG, 8‐OHdG and GSSG were significantly higher in apical periodontitis lesions compared to healthy pulp controls ( P = 0.001, P < 0.001, P < 0.001 and P < 0.05, respectively). RANKL and OPG mRNA expression was significantly higher in EBV‐positive compared to EBV‐negative periapical lesions ( P < 0.05). There was no significant correlation between EBV copy numbers and levels of RANKL, OPG, 8OH‐dG and GSSG in apical periodontitis. Conclusion: Levels of bone resorption regulators and oxidative stress biomarkers were increased in apical periodontitis compared to healthy pulp tissues. EBV‐positive periapical lesions exhibited higher levels of RANKL and OPG compared to EBV‐negative periapical lesions. EBV may contribute to progression of apical periodontitis via enhanced production of bone resorption regulators.